Youth lost to homicides: disparities in survival in Latin America and the Caribbean - Vladimir Canudas-Romo; José Manuel Aburto (BMJ Global Health)
Introduction The homicide rates among young men in Latin America and the Caribbean (LAC) are the highest in the world. It is not clear how this has impacted the life expectancy in these countries. This research has two purposes: (1) to quantify the impact of homicides on the mortality gap between LAC and high-income countries over recent years and (2) to assess the changes in homicide impact in overall survival over time.Methods Causes of death data were extracted for 23 countries in the LAC and 15 European countries (average European union-15 [EU-15]), using UN, UNODC, WHO, HMD and IHME databases for the period 2005–2014. The contribution by homicide deaths to the change in life expectancy, over time and as a difference between two populations, was quantified using decomposition methods.Results The contribution by homicide mortality to changes in life expectancy levels differed widely across the examined LAC countries. In Honduras, homicide mortality accounted for 1.75 (95% CI 1.64 to 1.86) and 6.30 (95% CI 6.07 to 6.53) years lower life expectancy than in the EU-15 countries for women and men, respectively. Contrary to this, homicide was just accountable for less than a couple of months of life expectancy differences between Chile and EU-15. Jamaica had the largest reduction in homicides and its impact increased life expectancy over time by almost half a year for men. However, Mexican men and Honduran women have experienced increases in mortality by homicide, which decreased their life expectancy by more than a quarter of a year between 2005 and 2014.Conclusions Excess mortality related to homicides in young people accounted for major changes in life expectancy in the LAC region. Furthermore, reducing excess mortality due to homicides is a crucial goal to further increase longevity towards levels of low-mortality countries. These reductions might prevent homicides spreading to other parts of Latin America. Decision and policy-makers in LAC need to address this immediately, and investing in the young population needs to be given a high priority.